2018
DOI: 10.1108/jpbafm-06-2018-027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the GASB No. 34 infrastructure reporting standards on state highway infrastructure quality

Abstract: Purpose The purpose of this paper is to evaluate whether the additional infrastructure information in US state financial statements improves infrastructure quality. Design/methodology/approach Based on institutional theory, the authors developed six models and estimated them on a state panel data set. Findings The authors found that the implementation of the Government Accounting Standard Board (GASB) Statement No. 34 improved state highway infrastructure quality, and the states using the modified approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 60 publications
(62 reference statements)
0
18
0
Order By: Relevance
“…Good asset maintenance depends on good information. Without knowing the condition of the assets, maintenance history, and so forth, it is difficult to adequately plan and budget for maintenance and replacement, or to be able to estimate the amount of deferred maintenance (Kim & Ebdon, 2017; Kim et al, 2018; Ostrom et al, 1993; Poterba, 1995). The GPP found that the lack of information systems for asset maintenance was a major issue for counties in 2001.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Good asset maintenance depends on good information. Without knowing the condition of the assets, maintenance history, and so forth, it is difficult to adequately plan and budget for maintenance and replacement, or to be able to estimate the amount of deferred maintenance (Kim & Ebdon, 2017; Kim et al, 2018; Ostrom et al, 1993; Poterba, 1995). The GPP found that the lack of information systems for asset maintenance was a major issue for counties in 2001.…”
Section: Resultsmentioning
confidence: 99%
“…Another study found that GASB 34 increased state highway capital spending, but did not have a significant effect on maintenance spending, which is somewhat surprising (Kim & Ebdon, 2017). GASB 34 was also found to have a positive effect on state highway quality (both directly and indirectly through spending), with a stronger effect in states using the modified reporting approach (Kim et al, 2018). The use of the modified approach was also found to reduce bid spreads for municipal bonds (Bloch et al, 2016) and to affect bond ratings (Benson & Marks, 2017).…”
Section: Literature Reviewmentioning
confidence: 97%
“…Besides these studies that focus on the motivation or the determinants for adopting different types of governments' infrastructure reporting, there is scant literature exploring the effects of implementing governments' infrastructure reporting. For instance, Kim et al (2018) find that the implementation of GASB 34 is positively and significantly associated with the share of good roads in state-administered highway systems, and this effect is larger for states using the modified approach than those using depreciation accounting methods. Kim and Ebdon (2017) contend that the implementation of GASB 34 significantly increased total highway expenditures.…”
Section: Previous Literaturementioning
confidence: 99%
“…Scholars normatively and empirically suggest that the infrastructure reporting requirements are useful to reduce the information problem and thereby improve state highway investment and quality (see Bloch et al, 2016;Dornan, 2002Dornan, , 2008Kim & Ebdon, 2017;Kim et al, 2018;Koechling, 2004;Kraus, 2004;Wilson & Kattelus, 2001). For instance, Dornan (2002) argues that GASB No.…”
Section: Routine Maintenance Spendingmentioning
confidence: 99%